DEVELOPMENT OF A SCIENTIFIC LITERACY-BASED ETHNOSCIENCE E-LKPD FOR JUNIOR HIGH SCHOOL SCIENCE ON TEMPERATURE, HEAT, AND THERMAL EXPANSION - Regina Atikoh Cahyani; Skunda Diliarosta; Tuti Lestari; Yurnetti Yurnetti (Universe, 2026)
The implementation of Kurikulum Merdeka emphasizes student-centered learning, requiring learners to be more active, independent, and capable of utilizing digital technology in the learning process. However, students' scientific literacy remains low, as indicated by the 2018 Programme for International Student Assessment (PISA) results, while their understanding of local ethnoscientific knowledge is still limited. This study aimed to develop a scientific literacy-based electronic student worksheet (E-LKPD) integrating ethnoscience for junior high school science learning on the topic of temperature, heat, and thermal expansion. The study employed a Research and Development (R&D) approach using the ADDIE model, comprising the Analyze, Design, and Development stages. The product was evaluated through validity and practicality tests involving three expert validators, five science teachers, and 32 eighth-grade students at SMP Negeri 9 Padang. Data were collected using validity and practicality questionnaires and analyzed using the Cohen's kappa coefficient. The results showed that the developed E-LKPD achieved a validity coefficient of 0.85, indicating very high validity, while the practicality coefficients were 0.93 from teachers and 0.87 from students, both categorized as very practical. These findings indicate that the developed scientific literacy-based E-LKPD integrating ethnoscience is valid and practical for supporting junior high school science learning on the topic of temperature, heat, and thermal expansion.